2017
DOI: 10.1088/1741-2552/aa7fc5
|View full text |Cite
|
Sign up to set email alerts
|

BrainFrame: a node-level heterogeneous accelerator platform for neuron simulations

Abstract: The BrainFrame framework is designed to transparently configure and select the appropriate back-end accelerator technology for use per simulation run. The PyNN integration provides a familiar bridge to the vast number of models already available. Additionally, it gives a clear roadmap for extending the platform support beyond the proof of concept, with improved usability and directly useful features to the computational-neuroscience community, paving the way for wider adoption.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
2

Relationship

4
4

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 27 publications
0
27
0
Order By: Relevance
“…It is shown that when density grows, even more floating-point operations need to be performed to simulate the model. It also reveals that the model is compute bound for larger densities [29]. This makes it an excellent target for HPC fabrics such as the GPU.…”
Section: Multi-node Accelerator Technologymentioning
confidence: 86%
See 2 more Smart Citations
“…It is shown that when density grows, even more floating-point operations need to be performed to simulate the model. It also reveals that the model is compute bound for larger densities [29]. This makes it an excellent target for HPC fabrics such as the GPU.…”
Section: Multi-node Accelerator Technologymentioning
confidence: 86%
“…The goal of our work is BrainFrame, which is a heterogeneous acceleration platform that incorporates three distinct acceleration technologies, Intel Xeon-Phi CPUs, NVIDIA GP-GPUs, and Maxeler Dataflow Engines (DFEs). So far, we have simulated the ION model on a single-node GPU [7], Xeon-Phi [29], and DFE [30] setup as well as on a multi-node (eight-way) Xeon-Phi [1] setup. Eventually, BrainFrame will move toward multi-node heterogeneity and into the Cloud for all to access.…”
Section: Related Work: Survey Of Neural-network Simulatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…This work is the first, to our knowledge, to extensively study the scaling differences between two different AdEx network configurations; an externally stimulated network as well as a self-stimulated one. Furthermore, the simulator is part of an effort to develop an acceleration platform for computationally challenging neuroscientific simulations [7].…”
Section: Related Workmentioning
confidence: 99%
“…The simulation of massive dense networks of the neuron model is very challenging, due to the high demand in floating-point operations per simulation cycle. Single-node deployments in multiple platforms [29], include x86-based architectures (Intel Xeon and Intel Xeon Phi), GPUs and MAX DFEs. The simulation will be used during the implementation and the early evaluation of the heterogeneity and multi-node extensions of the EXA2PRO environment.…”
Section: Exa2pro Benchmarksmentioning
confidence: 99%